A Corpus-Based Approach to Clause Combining in English from the Systemic Functional Perspective - He, Qingshun; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents corpus-based research on functional syntax. It is the first book to present a comprehensive investigation into grammatical metaphor in English clause combining in large-size corpora. By providing a systematic illustration of features such as parataxis, hypotaxis and embedding, it fills a gap in the systemic functional literature. It also offers insights into testing grammatical metaphors using a corpus linguistics methodology. The book is a useful resource for anyone interested in writing development. .
Chapter 1 Introduction -- Chapter 2 A Systemic Functional Approach to Clause Combining in English -- Chapter 3 Research Design -- Chapter 4 Genre Distributions of Clause Combining -- Chapter 5 Diachronic Distribution of Clause Combining -- Chapter 6 Grammatical Metaphor in Clause Combining -- Chapter 7 Conclusion.
Keywords: Grammar, Comparative and general -- Syntax; Computational linguistics; Germanic languages; Syntax; Computational Linguistics; Germanic Languages